2003
DOI: 10.1007/s00402-003-0586-9
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary fixation of pertrochanteric hip fractures with the short AO-ASIF proximal femoral nail

Abstract: In view of only one loss of reduction with varus collapse clearly caused by a technical error, we concluded that the PFN is a suitable implant for unstable fractures, but the high re-operation rate precludes its routine use for every pertrochanteric fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
176
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 37 publications
3
176
0
11
Order By: Relevance
“…They also reported heterotopic ossification in two patients fixed with PFN. 19 Simmermacher et al in a clinical multicenter study, reported technical failures of the PFN after poor reduction, malrotation or wrong choice of screws in 5% of the cases. A cut-out of the neck screw occurred in 0.6%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also reported heterotopic ossification in two patients fixed with PFN. 19 Simmermacher et al in a clinical multicenter study, reported technical failures of the PFN after poor reduction, malrotation or wrong choice of screws in 5% of the cases. A cut-out of the neck screw occurred in 0.6%.…”
Section: Discussionmentioning
confidence: 98%
“…19 Kamboj et al studied 30 cases, in one case with trochanteric fracture extending to diaphysis encirclage wiring was done. One patient got intra operative fracture shaft of femur, three patients had poor placement of screw.…”
Section: Discussionmentioning
confidence: 99%
“…As principais complicações encontradas em nosso estudo estão em acordo com as publicações anteriores sobre este tipo de implante, as quais revelam taxa de cutout variando entre 0,7 e 10,6%, e de fratura da diá-fise abaixo da ponta da haste entre 0 a 2,1% (20)(21)(22)(23)(24)(25)(26)(27) . Em nossa casuística encontramos apenas um caso de cutout (2,2%) e nenhum caso de fratura do implante.…”
Section: Discussionunclassified
“…Other studies have also reported femoral shaft fracture rates of 0-2.1 percent. 14,15 The only complications we encountered in this series were malunion, screw back out and wound infection.…”
Section: Resultsmentioning
confidence: 74%